Future Nuisance Flooding in Norfolk, VA, From Astronomical Tides and Annual to Decadal Internal Climate Variability. Issue 22 (28th November 2018) - Burgos, A. G.; Hamlington, B. D.; Thompson, P. R.; Ray, R. D.
Abstract: Increasing sea level rise will lead to more instances of nuisance flooding along the Virginia coastline in the coming decades, causing road closures and deteriorating infrastructure. These minor flood events can be caused by astronomical tides alone, in addition to internal climate variability on annual to decadal timescales. An assessment of nuisance flooding from these two effects is presented up until the year 2050 for Norfolk, Virginia. The analysis of water levels indicates that nuisance flooding from tides alone in conjunction with a medium‐high sea level scenario will result in flooding beginning in 2030 with frequency increasing thereafter. The addition of climate variability, by use of an empirical mode decomposition, leads to a substantial increase of flooding relative to the tides‐alone analysis and shows flood events beginning as soon as 2020. High tides in the future will produce nuisance flooding without the need of other drivers such as coastal storms. Plain Language Summary: As sea level continues to rise, coastal cities are going to start to see increases in nuisance flooding. This minor flooding is generally caused by tides and wind events, leading to inundation that over time deteriorates roads and infrastructure. Nuisance flooding in Norfolk, Virginia, has increased 325% since 1960 and is becoming more prominent. By combining sea level estimates, tidal estimates, and natural internal climate variability contributions to sea level rise, we have determined how nuisance flooding will increase in the future for Norfolk up until the year 2050. Our analyses show that this flooding will continue to increase in frequency with time, with a potential for well over 200 flood events in the year 2049. Key Points: Nuisance flooding can occur from high tides alone in Norfolk starting in the year 2030 with a sea level rise of 18 cm Internal climate variability can increase nuisance flooding by 126% compared to tides alone in Norfolk with a medium sea level rise of 40 cm